Analisis Pengaruh Brand Image Dan Product Quality Terhadap Keputusan Pembelian Konsumen Kebab Turki Baba Rafi Melalui Variabel Intervening Word Of Mouth (Studi Kasus Konsumen Kebab Turki Baba Rafi Soekarno Hatta Malang): Studi Kasus Konsumen Kebab Turki Baba Rafi Soekarno Hatta Malang - Romadhon, Khoirul; Nuzil, Nur Rohmat (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2022)
The purpose of this study was to determine the direct and indirect effect of brand image,product quality, word of mouth variables on purchasing decisions. The population in this study were consumers of Kebab Turki Baba Rafi Soekarno Hatta Malang. Sampling in this study used the Lemeshow formula with purposive sampling method, the result were 100 respondents. Data analysis techniques in this study used descriptive statistical analysis, classical assumption test, and path analysis. It can be concluded that (1) there is a positive and significant influence between brand image and product quality on word of mouth, (2) there is a positive and significant influence between brand image and product quality on purchasing decisions, (3) there is a positive and significant influence There is a significant relationship between word of mouth on purchasing decisions, (4) there is a positive and significant influence between brand image and product quality on purchasing decisions through the variable intervening word of mouth.